Carbon Source Starvation of a Sulfate-Reducing Bacterium–Elevated MIC Deterioration of Tensile Strength and Strain of X80 Pipeline Steel - Li, Zhong; Yang, Jike; Guo, Huihua; Kumseranee, Sith; Punpruk, Suchada; Mohamed, Magdy E.; Saleh, Mazen A.; Gu, Tingyue (Frontiers in Materials, 2021)
It is known that starved SRB biofilms corrode carbon steel more aggressively because they use electrons from elemental iron oxidation as an alternative source of energy. This work used carbon source starvation to vary MIC severity for studying the subsequent MIC impact on the degradation of X80 carbon steel mechanical properites. X80 square coupons and dogbone coupons were immersed in ATCC 1249 culture medium (200 mL in 450 mL anaerobic bottles) inoculated with Desulfovibrio vulgaris for 3-day pre-growth and then for additional 14 days in fresh media with adjusted carbon source levels for starvation testing. After the starvation test, the sessile cell counts (cells/cm2) on dogbone coupons in the bottles with carbon source levels of 0%, 10%, 50% and 100% (vs. that in the full-strength medium) were 8.1×106, 3.2×107, 8.3×107 and 1.3×108, respectively. The pit depths from X80 dogbone coupons were 1.9 μm (0%), 4.9 μm (10%), 9.1 μm (50%) and 6.4 μm (100%). The corresponding weight losses (mg/cm2) from the square coupons were 1.9 (0%), 3.3 (10%), 4.4 (50%) and 3.7 (100%). The 50% carbon source level had the combination of carbon starvation without suffering too much sessile cell loss. Thus, its pit depth and weight loss were both the highest. Electrochemical tests corroborated the pit depth and weight loss trends. Tensile tests of the dogbone coupons after the starvation incubation indicated that SRB made X80 more brittle and weaker. Compared with the fresh X80 dogbone coupon’s ultimate tensile strain of 23.9% and ultimate tensile stress of 860 MPa, the 50% carbon source level led to the lowest ultimate tensile strain of 18.4% (23% loss compared to fresh dogbone) and ultimate tensile stress of 672 MPa (22% loss). The 100% carbon source level had a smaller loss in ultimate tensile strain than 50%, followed by 10% and 0%. Moreover, the 100% carbon source level had a smaller loss in ultimate tensile strength than 50%, followed by 10% and 0% in a tie. This outcome shows that even in the 17-day short-term test, significant degradation of mechanical properties occurred, and more severe MIC pitting caused more severe degradation.